Control interno de la cartera vencida de Inplanet S.A. en la ciudad de Babahoyo, del periodo 2022. - Torres Bravo, Shirley Yanine (2023)
The following case study carried out at the Inplanet S.A. Located in the city of Babahoyo, its theme is the internal control of past-due portfolio, where the problem found through the interview that was carried out with the branch workers is explained, in the work carried out a problem tree is shown where the problems and effects within the organization are detailed.In the work it is explained and supported based on the specific objectives, in the first instance the overdue portfolio is examined, which is detailed in an explanatory table where the classification of the client portfolio is shown, and values in dollars that it represents for Inplanet. Through the interview and survey method, the procedures carried out by the collection department to carry out internal control within accounts receivable are identified and, finally, recommendations for effective strategies are expressed for the optimal control of the overdue portfolio.